MEMBANGUN BUDAYA ORGANISASI - Hasnan Nafis (Jurnal Tunas Pendidikan, 2020)
Study to organizational cultural congeniality also assure organizational cultural role as ameans of to determine organizational direction, instructing what may and not may be conducted, how and manage resourceorganizational allocation as well as a means of to face incoming oppurtunity and problem from organizational environment, especially the strength stem from organizational basal values.